Kuat lentur dan berat jenis beton ringan selular diperkuat serat kain pakaian bekas - A. D. Catur; P. D. Setyawan; Y. A. Padang; I. M. Nuarsa; A.A. A. Triadi (Universitas Mataram, 2022)
Cellular lightweight concrete has an advantage in its specific gravity, with the presence of foam making it lighter. However, the presence of foam reduces its strength. Utilization of used clothing fibers is carried out to increase the flexural strength of cellular lightweight concrete and is useful for reducing environmental loads. Used clothing fibers are added to the cellular lightweight concrete in the amount of 0%; 0.3%; 0.6%; 0.9% and 1.2% of weight. Cellular lightweight concrete is also reinforced with steel wire mesh with a wire diameter of 0.5 mm with a side length of ¼ inch x ¼ inch. With the addition of used clothing fibers increase the flexural strength and reduce the density of cellular lightweight concrete. The addition of steel wire mesh increases the flexural strength but increases the density of cellular lightweight concrete.